Caprine Monocytes Release Extracellular Traps against Neospora caninum In Vitro - Yang, Zhengtao; Wei, Zhengkai; Hermosilla, Carlos; Taubert, Anja; He, Xuexiu; Wang, Xiaocen; Gong, Pengtao; Li, Jianhua; Zhang, Xichen (Frontiers in Immunology, 2018)
Neospora caninum is an obligate intracellular apicomplexan parasite that causes reproductive loss and severe economic losses in dairy and goat industry. In the present study, we aim to investigate the effects of N. caninum tachyzoites on the release of extracellular traps (ETs) in caprine monocytes and furthermore elucidated parts of its molecular mechanisms. N. caninum tachyzoite-induced monocytes-derived ETs formation was detected by scanning electron microscopy. H3 and myeloperoxidase (MPO) within monocyte-ETs structures were examined using laser scanning confocal microscopy analyses. The results showed that N. caninum tachyzoites were not only able to trigger ETs formation in caprine monocytes, but also that monocyte-released ETs were capable of entrapping viable tachyzoites. Histones and MPO were found to be decorating the DNA within the monocytes derived-ETs structures thus proving the classical components of ETs. Furthermore, inhibitors of NADPH oxidase-, MPO-, ERK 1/2-, or p38 MAPK-signaling pathway significantly decreased N. caninum tachyzoite-triggered caprine monocyte-derived ETosis. This is the first report of ETs release extruded from caprine monocytes after N. caninum exposure and thus showing that this early innate immune effector mechanism might be relevant during the acute phase of caprine neosporosis.